2018
DOI: 10.1504/ijaf.2018.10014470
|View full text |Cite
|
Sign up to set email alerts
|

The impact of risk committee on financial performance of UK financial institutions

Abstract: Following the recent financial crisis, Walker (2009) recommended that financial institutions should form a separate board level risk committee (RC) to manage various risks and prevent excessive risk taking. This research focuses on investigating how firms with separate risk committees differ from those that do not have one. The main research question we address is whether RCs have a fundamental influence on financial performance. We measure financial performance by ROA and ROE and we control for firm size, liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…This study will focus specifically to the banking industry in Kenya and the findings will be generalised to the banking industry in Kenya. Another study done by (Elamer & Benyazid (2018) on impact of risk commmittee on financial performance of UK financial institutions found that institutions with existence of risk committee performed poorly compared with institutions that did not have risk committees. This study cincluded that risk committee existence is negatively related to financial perforemnce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study will focus specifically to the banking industry in Kenya and the findings will be generalised to the banking industry in Kenya. Another study done by (Elamer & Benyazid (2018) on impact of risk commmittee on financial performance of UK financial institutions found that institutions with existence of risk committee performed poorly compared with institutions that did not have risk committees. This study cincluded that risk committee existence is negatively related to financial perforemnce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The corporate governance mechanisms quality is the central influencing factor of corporate financial policies, including cash holding (Abdelfattah et al 2020 ; Abdou et al 2020 ; AlHares et al 2020 2020a ; Alnabsha et al 2018 ; Alshbili et al 2019 ; Alshbili and Elamer 2020 ; Hazaea, Zhu, et al , b ; Khatib et al 2020 ). Corporate governance practices are expected to ensure that executives act in the best interest of stockholders (Asante-Darko et al 2018 ; Bufarwa et al 2020 ; El-Dyasty and Elamer 2020 ; Elamer et al 2018 , 2020 , 2019 ; Elamer and Benyazid 2018 ; Elmagrhi et al 2018 ; Hazaea et al 2020a ). Jensen ( 1986 ) stressed that executives are reluctant to disburse the extra cash among stockholders to secure their benefits by investing it in unprofitable projects, which might destroy corporates' valuation.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…First, the formation of a risk committee in the organizational structure will improve the company's financial performance (Jia & Bradbury, 2020). Second, companies that have a separate risk committee (RC) will form communication problems and cause conflicts within the company, which will reduce the company's financial performance (Elamer & Benyazid, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Company performance is measured based on the ROA value and Tobin's Q value (Aldhamari et al, 2020). ROA is calculated based on the comparison of the value of net income and total assets (Elamer & Benyazid, 2018). While the value of Tobin's Q is defined as the sum of the total market value of equity and book value of total debt divided by the value of total assets (Aldhamari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation